2006
DOI: 10.1182/blood-2006-02-003145
|View full text |Cite
|
Sign up to set email alerts
|

Functional ABCG2 is overexpressed on primary CML CD34+ cells and is inhibited by imatinib mesylate

Abstract: IntroductionThe introduction of imatinib mesylate (IM) has transformed the treatment of chronic myeloid leukemia (CML), however a significant minority of patients does not respond and others lose response during treatment. Such states reflect IM resistance in the whole cell population, however suboptimal responses may represent the persistence of a subpopulation of insensitive leukemic stem cells (LSCs). [1][2][3][4] One possible mechanism of LSC persistence is the limitation of intracellular drug concentratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
116
1
4

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 152 publications
(127 citation statements)
references
References 17 publications
3
116
1
4
Order By: Relevance
“…It has now been demonstrated that SP cells are present in several tumour samples, possess stem cell-like properties, overexpress BCRP and possess inherent drug resistance (Haraguchi et al, 2006). Consistently, BCRP overexpression was reported on primary CML CD34 þ cells (Jordanides et al, 2006). Imatinib is efficiently used in the clinical treatment of BCR-ABL-driven CML, but possible BCRP-mediated imatinib resistance would naturally affect the efficacy of the treatment.…”
Section: Bcrp In Stem Cellsmentioning
confidence: 81%
See 1 more Smart Citation
“…It has now been demonstrated that SP cells are present in several tumour samples, possess stem cell-like properties, overexpress BCRP and possess inherent drug resistance (Haraguchi et al, 2006). Consistently, BCRP overexpression was reported on primary CML CD34 þ cells (Jordanides et al, 2006). Imatinib is efficiently used in the clinical treatment of BCR-ABL-driven CML, but possible BCRP-mediated imatinib resistance would naturally affect the efficacy of the treatment.…”
Section: Bcrp In Stem Cellsmentioning
confidence: 81%
“…Rather, imatinib may serve as a potent BCRP inhibitor thereby enabling reversal of BCRP-mediated resistance to topotecan and SN-38 (Houghton et al, 2004). Similarly, accumulation of mitoxantrone in primary chronic myeloid leukaemia (CML) CD34 þ cells overexpressing BCRP was significantly increased by 5 mM of imatinib, confirming the activity of this TKI as a BCRP inhibitor (Jordanides et al, 2006). The same authors postulated that imatinib is not a BCRP substrate, since BCRP inhibition in CML CD34 þ cells neither potentiated the effect of imatinib nor affected imatinib accumulation in these cells.…”
Section: Imatinibmentioning
confidence: 92%
“…50,51 Moreover, both transporters show elevated expression in CML stem cells, 52,53 and several known SNPs modify 56 Although they did not investigate the relationship between the tested SNPs and plasma IM concentration, the authors noted that interindividual variation in hepatic IM uptake and clearance could lead to changes in systemic IM concentration. Our results should be interpreted within the context of the study limitations, which primarily involve the sample size of the study.…”
Section: Discussionmentioning
confidence: 99%
“…Imatinib has been variably reported to be a substrate and/or an inhibitor for the BCRP/ABCG2 drug efflux pump, which is overexpressed in many human tumors and also found to be functionally expressed in CML stem cells [111,112]. CML stem cells have been shown to express the ATP dependent transporter cassette protein ABCG2, which could decrease the intracellular accumulation of Imatinib in CML LSC [103].…”
Section: Drug Effluxmentioning
confidence: 99%